BUILDING STUDENTS' SAVING HABITS THROUGH FINANCIAL LITERACY SOCIALIZATION IN JUNIOR HIGH SCHOOL 11 MALANG CITY - Kurniawan, Novian Candra; Idris; Ni’matuzzuriyah; Ratna Nur’Aini; Irna Inaru; Khoridatul Khasanah; Muhammad Ajriansyah; Maria Melita Ratni Jemalu; Maria Yustika Mijang; Muhammad Angga Rizqi (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Financial literacy is an important factor for learners in the era of Society 5. 0.. Learners' tendency to buy things they want rather than things they need is a problem for them. Therefore, it is important to provide early knowledge about financial literacy to students. The activities carried out use socialization about the importance of financial literacy using resource persons and flip book socialization developed by the activity implementer.  The socialization was carried out, using 3 stages (preparation, implementation and evaluation of activities) with the target of activities on students at SMP Negeri 11 Malang. Then, the implementation method carried out is providing material about the importance of financial literacy from an early age to students. As a result, the activity carried out on May 17, 2024, gave a positive response for students by 96%. Thus, the activities carried out went well and had a positive impact on students. These results provide meaning if the socialization carried out can increase knowledge about financial literacy for students.